Body mass index impacts ectopic pregnancy during in vitro fertilization: an analysis of 42,362 clinical pregnancy cycles - Ge, Xiaofei; Wang, Keyan; Sun, Yingpu; Bu, Zhiqin (Reproductive biology and endocrinology, 2023)
Purpose This large, single-center, retrospective cohort study was aimed to explore the effect of female body mass index (BMI) on ectopic pregnancy (EP) following fresh and frozen-thawed embryo transfers (ET). Methods A total of 27,600 pregnancies after fresh ET and 14,762 pregnancies after frozen-thawed ET were included between January 2010 to June 2022. Women were divided into three groups based on BMI according to the Working Group on Obesity in China (WGOC), International Life Sciences Institute (ILSI): underweight (BMI < 18.5 kg/m.sup.2), normal weight (BMI, 18.5-23.9 kg/m.sup.2), and overweight or obesity ([greater than or equal to] 24 kg/m.sup.2). Compare EP rates among BMI categories in fresh and frozen-thawed ET cycles respectively. Multivariate logistic regression analyses were used to investigate the association between female BMI and EP. Results The overall EP rates in fresh, and frozen thawed transfer cycles were 2.43% (672/27,600) and 2.82% (417/14,762), respectively. In fresh ET cycles, underweight women yielded a significantly higher EP rate than those with normal and excess weight (3.29% vs. 2.29% vs. 2.54%, P = 0.029). But EP rates did not differ among the three BMI groups (2.72% vs. 2.76% vs. 2.96%, P = 0.782) in frozen-thawed ET cycles. In fresh ET cycles, after adjusting for potential confounding factors, no significant association was found between female BMI and EP occurrence (adjusted OR: 0.98, 95% CI 0.70-1.37, P = 0.894, for BMI 18.5-23.9 kg/m.sup.2; adjusted OR: 0.89, 95% CI 0.75-1.06, P = 0.205, for BMI [greater than or equal to] 24 kg/m.sup.2. Reference = BMI < 18.5 kg/m.sup.2). Conclusion(s) Female BMI did not affect the occurrence of ectopic pregnancy in either fresh or frozen-thawed embryo transfer cycles. Keywords: Female BMI, Ectopic pregnancy, IVF/ICSI, Embryo transfer